Reflection of Tri Hita Karana Philosophy as A Local Wisdom of Bali Communities in Responding to Social Conflict in The Global Reform Era - I Gusti Ayu Suarniati; I Gusti Ngurah Anom; I Gusti Bagus Hengki (Sociological Jurisprudence Journal, 2019)
The development of science and technology, communication, transportation, and entering the era of global reform bring positive and negative effect to the world community, in community of developed country or developing country like Indonesia which has plural society that different language, etnic, customs, and religion which certainly brings the highest impact of social conflict in the intern or ekstern. Bali and the society that heterogeneousas from the territory of Indonesia can not avoid negative effect from global community, among them is social conflict in the name of ‘adat’. Reflection of philosophy ‘Tri Hita Karana’ as local wisdom in tackling social conflict in the name of ‘adat’ in the era of global reform, must be discussed, reviewed, analyzed through a scientific study can later be expected to become foundation in searching a right solution for the sake of solid NKRI that based on Pancasila ideology, UUD 1945 and Bhineka Tunggal Ika.